Adipophilin expression in lung adenocarcinoma is associated with apocrine‐like features and poor clinical prognosis: an immunohistochemical study of 328 cases. Issue 2 (27th September 2016) - Fujimoto, Masakazu; Yoshizawa, Akihiko; Sumiyoshi, Shinji; Sonobe, Makoto; Menju, Toshi; Hirata, Masahiro; Momose, Masanobu; Date, Hiroshi; Haga, Hironori
Abstract : Aims: The lipogenic pathway is up‐regulated in proliferating cells. However, the clinical impact of neoplastic steatogenesis in lung cancer is unclear. The aim of the present study was to evaluate the association of intracytoplasmic lipids with the clinicopathological features of lung adenocarcinoma (ADC), by immunohistochemical analysis of adipophilin (ADP), a coating protein found on intracytoplasmic lipid droplets. Methods and results: Tissue microarrays consisting of 328 primary lung ADCs surgically resected at Kyoto University Hospital were immunostained for ADP. Subsequently, correlations between ADP expression and clinical, molecular and survival data were performed. Fifty‐one (15.5%) cases were ADP‐positive. The presence of vascular invasion ( P = 0.003), predominantly solid histology ( P < 0.001), poorly differentiated type ( P < 0.001), wild‐type EGFR ( P = 0.002), ALK fusion ( P < 0.001), strong/diffuse mitochondrial staining ( P < 0.001), a lack of surfactant protein B expression ( P = 0.014) and a high Ki67 index ( P < 0.001) were significantly correlated with ADP‐positive ADC. In contrast, there were no correlations between ADP‐positive ADC and sex, age, smoking history, tumour stage, thyroid transcription factor‐1 expression, or KRAS mutational status. ADP‐positive ADCs had apocrine‐like features ( P < 0.001). Patients with ADP‐positive ADC had worse disease‐free and overall survival ( P = 0.047 and P = 0.013, respectively) than those with ADP‐negative ADC. Conclusions: ADP was expressed in a small proportion of lung ADCs. ADP‐positive lung ADC was significantly associated with apocrine‐like features, wild‐type EGFR, and poor prognosis, suggesting that ADP‐positive lung ADC could be a distinct subtype of lung adenocarcinoma, induced by up‐regulation of the lipogenic pathway.